Development of Evaluation Indicators for Logistic Transportation System with Triple Bottom Line Approach: Jakarta Study Case - Julian, Muhammad Hafiz Risat; Nahry, Nahry (Prodi Teknik Sipil, Fakultas Teknik, Universitas Jember dan Forum Studi Transportasi antar Perguruan Tinggi, 2024)
Jakarta has significant problems related to logistics transportation, including congestion, environmental pollution, and the negative impact of operating overloaded trucks. To overcome these externalities, it is necessary to have an urban logistics system and planning cycle that considers the concept of sustainability. This study aims to propose an arrangement of indicators as a tool for evaluating the urban logistics transportation system. The research was carried out through a literature study process, identification of the long list of indicators and selection criteria, independent selection, surveys and interviews, ranking with the VIKOR Method, and validation with expert considerations. A final set of indicators was produced, namely ten indicators, divided into economic, social, and environmental aspects, for evaluating the sustainability of the city's logistics transportation system. This research is helpful as input in developing a set of indicators for evaluating the logistics transportation system in urban areas, especially in Jakarta Capital Special Region. ABSTRAK Jakarta memiliki permasalahan signifikan terkait transportasi logistik, antara lain kemacetan, pencemaran lingkungan, dan dampak negatif pengoperasian truk dengan muatan berlebih. Untuk mengatasi eksternalitas tersebut, diperlukan sistem logistik perkotaan dan siklus perencanaan yang mempertimbangkan konsep keberlanjutan. Penelitian ini bertujuan untuk mengusulkan suatu susunan indikator sebagai alat bantu evaluasi sistem transportasi logistik perkotaan. Penelitian dilakukan melalui proses studi literatur, identifikasi Long-list indikator dan kriteria seleksi, seleksi mandiri, survei dan wawancara, pemeringkatan dengan Metode VIKOR, dan validasi dengan pertimbangan para ahli. Dihasilkan seperangkat indikator akhir, yaitu sepuluh indikator yang terbagi dalam aspek ekonomi, sosial, dan lingkungan untuk menilai keberlanjutan sistem transportasi logistik kota. Penelitian ini bermanfaat sebagai masukan dalam mengembangkan seperangkat indikator untuk mengevaluasi sistem transportasi logistik di perkotaan, khususnya di Daerah Khusus Ibukota Jakarta.